There is no such Revival. Around the Philosophical Disquisitions on Alienation in the late Twentieth Century - Ache, Sofía (2021)
The following paper proposes to give arguments to relativize the extensive account that the concept of alienation lost theoretical attention in the field of philosophy during the eighties of the last century, and that a revival of the study of the concept occurred in the nineties. The conclusion is that there was no such loss of attention, but that furthermore, the presumed premises in the discussion concerning alienation from the nineties up to the present were delineated during the eighties. This conclusion has two supporters: the type of approach regarding alienation carried out by analytical Marxism and the philosophical incursions into the concept in the context of North American sociology. Based on this, the text offers a systematization of the history of the philosophical study of the concept in two sections or stages. And it concerns itself with two –and not three– stages because, for what was argued, philosophy did not stop talking about alienation in the eighties, although it did so to a much lesser extent than before (specifically, during the sixties and seventies, considered the boom in the philosophical treatment of alienation).